2008
DOI: 10.1634/stemcells.2007-0795
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Mesenchymal Stem Cells Accelerate Recovery of Acute Renal Injury and Prolong Survival in Mice

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
281
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(301 citation statements)
references
References 60 publications
19
281
0
1
Order By: Relevance
“…Administration of heterologous MSCs confers a protective effect against AKI and a functional improvement in chronic kidney disease (CKD), but the explanation for these beneficial effects is still debated. Initially, it was thought that MSCs home to the kidney and replace damaged renal cells; in particular, in AKI induced by cisplatin 22,23 and glycerol, 24,25 a tubular engraftment of the injected MSCs has been observed. Subsequently, in the ischemia-reperfusion injury (IRI) model, evidence of differentiation of MSCs directly into tubular cells was not been detected, 26,27 and these data suggested that the MSCs do not replace renal tubular cells but mitigate injury by providing a paracrine support to the repair of injured ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Effect Of Mesenchymal Stem Cell-derived Mvs In Renal Regenermentioning
confidence: 99%
“…Administration of heterologous MSCs confers a protective effect against AKI and a functional improvement in chronic kidney disease (CKD), but the explanation for these beneficial effects is still debated. Initially, it was thought that MSCs home to the kidney and replace damaged renal cells; in particular, in AKI induced by cisplatin 22,23 and glycerol, 24,25 a tubular engraftment of the injected MSCs has been observed. Subsequently, in the ischemia-reperfusion injury (IRI) model, evidence of differentiation of MSCs directly into tubular cells was not been detected, 26,27 and these data suggested that the MSCs do not replace renal tubular cells but mitigate injury by providing a paracrine support to the repair of injured ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Effect Of Mesenchymal Stem Cell-derived Mvs In Renal Regenermentioning
confidence: 99%
“…Multipotent mesenchymal stromal cells (MSC), also known as mesenchymal stem cells [14], are bone marrow-derived precursor cells with the potential to differentiate into different mesenchymal lineages, such as adipocytes, chondroblasts and osteoblasts [15]. Because of their differentiation potential, MSC are of particular interest for cell-based therapies in different acute disorders such as myocardial infarction and acute renal failure [16,17]. Furthermore, MSC are known for their immunosuppressive and immunomodulatory potential during stem cell transplantation [18 -21].…”
mentioning
confidence: 99%
“…What is perhaps most pertinent, however, is that inflammatory demyelinated lesions were obvious throughout the CNS at this stage (day 50) and yet few or no hMSCs were disclosed. Rejection would be unlikely in view of the recognised immune suppressive effects of these cells [12]; others have likewise found no rejection of human MSCs in rodent recipients [8,17].…”
mentioning
confidence: 99%